(untitled) (Journal of Oriental Studies, 2025)
Objective reality, as well as the culture, history and traditions of a people, proverbs and sayings present in the minds of native speakers many phenomena and objects that can serve as a standard of proverbial character and quality, but most often images of the animal world are used as a standard of comparison. Zoonyms are often used in proverbs and sayings. In proverbs and sayings, zoonyms are the semantic center, their main meaning is metaphorical. Researchers are currently studying paremias containing zoonyms in one or several languages, comparing and contrasting phraseological units, proverbs, and proverbs. The object of our study is paremia, that is, proverbs and sayings. Animals live in nature alongside humans. Therefore, people attach great importance to animals, pay attention to their behavior, living conditions. Animals are divided into wild and domestic animals. They have their own characteristics, and are named accordingly, trying to convey the concept of the internal and external world of animals. The frequent use of proverbs, metaphorical, simile, and epithet expressions related to animals has expanded the scope of application of animal names in the language fund and made it possible to turn them into a special object of study. The Kazakh nation is a people that has developed in close contact with nature. Having been engaged in animal husbandry and living a nomadic life, the Kazakhs have certainly fully mastered the intricacies of nature. Therefore, animal names are often mentioned in folk literature, beliefs, rituals, and traditions. The Kazakh people have special respect for livestock. The ethnolinguistic, lexical-semantic, and linguocultural characteristics and contents of horses, cows, sheep, and goats and their offspring have been studied in depth. In addition, stable expressions and similes related to animals and birds are being studied to their full extent. Zoonyms, which are part of proverbs and sayings of different peoples, have national-ethnic and stylistic connotations. The peculiarities of Kazakh and Chinese understandings of the living world are also fixed in the way zoolexemes are formed, in the ability to express emotions and assessments with the help of suffixes (Kazakh) and suffixes, prefixes (Chinese). Keywords: paremia, proverb, saying, cultural connotation, animal, zoonym, vocabulary, semantics.